Procesos productivos en “la Corporación de Asociaciones de Campesinos la Pepa de Oro” - Chango Sellan, Ronald Rodrigo (2017)
Ecuador is recognized for its fine cocoa flavor quality, thus constituting a very considerable estimate in the Ecuadorean State budget, ranking as the third most important non-oil product in the country. The current case study has as its main scene the Peas de Oro Peas Associations Corporation of Vinces, a corporation that was created with the objective of promoting the relationship between organizations in such a way as to provide opportunities for families and communities, The purpose of this study is to analyze the "PRODUCTIVE PROCESSES IN THE CORPORATION OF ASSOCIATIONS OF CAMPESINOS PEPA DE GOLD", reason why we will give details in proportion to all the operations that are carried out on the methods for the elaboration of the chocolate, likewise the way in which it controls its production, records its inventories, and accounting procedures applied in the recording of accounting-financial information. In addition it was observed how they determine the cost of production, unit cost of the products and the level of income that each production has; through the inductive method and the technique of interview made to the production personnel.